Pengaruh Model Problem Based Learning Berbantuan Cabri Geometry 3D Terhadap Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa SD - Meiyunisa, Rika; Rohimah, Siti Maryam; Sunata (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2026)
This research was conducted to address the mathematical Low mathematical problem-solving attainment among Grade IV learners at SDN 066 Halimun provided the starting point for this investigation. The inquiry compared outcomes from two instructional settings: Problem-Based Learning integrated with Cabri Geometry 3D and conventional classroom teaching. It also examined the extent of improvement achieved by each class. The study adopted a quantitative quasi-experimental framework using a nonequivalent control group design. Fifty learners were chosen through purposive sampling, with 25 placed in the experimental class and 25 in the comparison class. Evidence was obtained from an eight-question constructed-response test and observations of classroom activity. IBM SPSS Statistics 29.0 was used to conduct normality and variance-homogeneity checks, an Independent Samples t-test, and normalized-gain analysis. The final-score comparison yielded a significance level below 0.001, confirming a meaningful difference between the classes. Normalized gain reached 0.62 for the experimental class and 0.34 for the comparison class; both fell within the moderate range, but the experimental increase was markedly larger. Within the limits of this study, combining problem-oriented learning with dynamic three-dimensional geometry supported mathematical problem solving more strongly than conventional instruction.